THE IMPORTANCE OF MONETARIST THEORY AND POLICY IN ECONOMIC REGULATION: https://doi.org/10.5281/zenodo.14506470 - Abdullaeva , Rita Rafaelevna (International scientific and practical conference, 2024)
Monetarism, as a school of thought in economics, emphasizes the central role of money supply in influencing economic activity, inflation, and overall economic performance. It was popularized by economist Milton Friedman in the mid-20th century and provided a counterpoint to Keynesian economics, which advocated for active fiscal intervention. Monetarist theory stresses the importance of controlling the money supply as the primary method for regulating inflation, stabilizing the economy, and achieving sustainable growth. This paper explores the key principles of monetarist theory, its policy implications, and the relevance of monetarism in modern economic regulation.